Investigation on transforming of a fixed gas analyser into a Portable Emission Measurement System (PEMS) - Choe, Sathit; Seyed, Amirmostafa Jourabchi; Ng, Hoon Kiat; Gan, Suyin (INTI International University, 2019)
Recently Portable Emission Measurement System (PEMS) is being used to show the real emission components of diesel engines (and petrol engines) instead of using test cycles because of their more realistic measurements. Their drawback is their high price and unavailability. This study investigates the possibility of transforming a fixed gas analyser that cost approximately RM50,000 into a PEMS. The project was done through the simulation of a program coded using Python to imitate the functions of a PEMS as close as possible. In the code, it is programmed to calculate emission from a diesel-based vehicle, based on the changes of the Torque and RPM. Simulation of the code uses data from a research paper reviewed. The difference of the project simulation and the research paper data is 6.32%. It is concluded there is a possibility as the code was able to be validated.